Beyond service education: Impacting the human experience with sustained training utilizing the Experience Model of Communication - Jennifer Packard; Rebecca Brustad; Jane Hoplin; Sheila Stevens (The Beryl Institute, 2022)
Patients scheduling or checking in for medical appointments often share with frontline employees' details of their stories, including their worries, prior negative experiences, and hopes. These interactions require employees to not only complete their task, but also to be mindfully present, picking up on important social cues and showing appropriate emotional congruence and empathic understanding. Based on a review of recorded patient calls, a gap was identified in the communication skills of desk and scheduling staff at this large academic medical center, and a sustained training program was created to fill this gap. The training is centered on an evolving set of theoretical principles and skills that have come to be known as the Experience Model of Communication (XMOC). We wanted to understand if training in XMOC, a set of skills essential for healthcare providers, would also be beneficial for frontline staff. The training was evaluated with pre/post surveys, listening sessions, an annual evaluation, and quarterly tracking of patient experience scores, and findings suggest that the training content has had a positive impact. We continue to build and evaluate the training program to identify and refine the elements that make up XMOC and the most effective ways to transfer that learning to the staff who benefit. Experience Framework This article is associated with the Staff & Provider Engagement lens of The Beryl Institute Experience Framework (https://www.theberylinstitute.org/ExperienceFramework). <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_20%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%2C%22Staff%20%26%20Provider%20Engagement%22%5D%7D%2C%7B%22field%22%3A%22field_41%22%2C%22operator%22%3A%22is%22%2C%22value%22%3A%5B%22%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens.